Spirituality, religion and coping: studies on psychological well-being from educational perspectives - Ssekamanya, Siraje Abdallah (Institut Terjemahan & Buku Malaysia / IIUM, 2016)
This book is the compilation of materials on the role of religion in the areas of human well-being and coping with adverse life situations. The readers will find articles related to these aspects both timely and of great importance as we are stepping into an era full of uncertainties and of great turbulence. The articles are from the works of empirical research completed with observations and experimentation with revealed truth and spiritual experiences. This should provide the readers a holistic and wholesome solution to the problems of mankind. The collection of studies in this volume are efforts to find empirical evidence for the utility of religious beliefs and practices for mitigating, if not completely alleviating, human suffering as a result of both psychological and physical causes.